2018
DOI: 10.3389/fendo.2018.00512
|View full text |Cite
|
Sign up to set email alerts
|

Expression and Functional Analysis of the BCL2-Associated Agonist of Cell Death (BAD) Gene in the Sheep Ovary During the Reproductive Cycle

Abstract: Most ewes in China are seasonally polyestrous with normal ovulatory cycles, which is controlled by photoperiod (length of the daily light phase). These ewes are estrous in the short-day season and anestrus in the long-day season and cannot mate during anestrus. Thus seasonal breeding limits both diversification and intensification of production. If sheep can estrus all round year, it can be mated twice per year, which can greatly improve the economic benefits. To change seasonal estrus at the genetic level and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 46 publications
0
9
0
Order By: Relevance
“…In addition, FOXO3 depletion in GCs disrupts the normal ovarian follicular growth in mice [45], and a lower FOXO3 mRNA expression in GCs may lead to infertility in women [46]. BAD can reduce progesterone levels by promoting ovarian GC apoptosis in sheep [47]. Being TSC2-deficient in oocytes results in the depletion of follicles in early adulthood [48].…”
Section: Discussionmentioning
confidence: 99%
“…In addition, FOXO3 depletion in GCs disrupts the normal ovarian follicular growth in mice [45], and a lower FOXO3 mRNA expression in GCs may lead to infertility in women [46]. BAD can reduce progesterone levels by promoting ovarian GC apoptosis in sheep [47]. Being TSC2-deficient in oocytes results in the depletion of follicles in early adulthood [48].…”
Section: Discussionmentioning
confidence: 99%
“…In this study, we utilized a short fragment of murine BAD to construct the BRET sensor rather than the full-length BAD. Previous research has demonstrated that BAD overexpression leads to apoptosis in various cell types [43, 44] , and an advantage of using the BAD-112-136F is its inability to interact with its client BCL-2 proteins due to the lack of BH-3 domain, leading to reduced cytotoxicity [45] . Furthermore, it was not possible to detect BRET when the Rluc8 acceptor and mCitrine donor were fused to 14-3-3ζ and full-length BAD, respectively.…”
Section: Discussionmentioning
confidence: 99%
“…BCL2 is an inducer of cell proliferation and is synthesized in the mitochondria and localized at their membranes through Akt activation, where it influences cell survival by restricting the actions of pro-apoptotic proteins such as BCL2-homologous antagonist/killer (Bak), BCL2-like protein 4 (Bax), and cytochrome c. 73 BAD on the other hand forms a heterodimer with anti-apoptotic protein BCL2 and prevents it from restricting pro-apoptotic proteins. 74 Activation of the PI3K/Akt pathway phosphorylates BAD and restricts its activity. 74 Breast cancers have a high probability of forming metastases, and this is a major factor contributing to the mortality of women suffering from this type of cancer.…”
Section: Role Of Igf-1 In the Carcinogenesis Of Breast Cancermentioning
confidence: 99%
“…74 Activation of the PI3K/Akt pathway phosphorylates BAD and restricts its activity. 74 Breast cancers have a high probability of forming metastases, and this is a major factor contributing to the mortality of women suffering from this type of cancer. Thus, it is crucial to understand the mechanisms involved in the initiation of metastasis to design therapeutic strategies accordingly.…”
Section: Role Of Igf-1 In the Carcinogenesis Of Breast Cancermentioning
confidence: 99%